The effect of price discount, FOMO, pay later on impulse buying and cognitive dissonance post-purchase in commerce shopping among the millennial generation - Amini, Salama; Rahmawati, Alni (Edelweiss Applied Science and Technology, 2025)
This study seeks to understand how millennials on Shopee are driven to make impulsive purchases by "price discounts, FOMO, and pay-later options," and how these purchases influence their feelings afterward. Using a quantitative approach with a causal research design, data were collected through a Google link involving respondents who had shopped online. The study confirmed that price discounts and FOMO significantly influence consumers to buy impulsively, while the pay-later option also contributes to increasing the frequency of purchases. However, high impulse buying is associated with increased post-purchase cognitive dissonance, where consumers experience discomfort and regret after purchasing. This research yields crucial information that can help e-commerce platforms optimize their marketing strategies, understand consumer behavior, and highlight the need for consumer education to reduce the risk of cognitive dissonance. This study is intended to act as a key source for future research concerning consumer habits within the digital marketplace, which continues to grow.